History-based trust negotiation model - 赵贻竹 赵彦华 鲁宏伟 (Journal of Shanghai University, 2009)
Trust negotiation （TN） is an approach to establish trust between strangers through iterative disclosure of digital credentials. Speeding up subsequent negotiations between the same negotiators is a problem worth of research. This paper introduces the concept of visiting card, and presents a history-based trust negotiation （HBTN） model. HBTN creates an account for a counterpart at the first negotiation and records valid credentials that the counterpart disclosed during each trust negotiation in his historical information base （HIB）. For the following negotiation, no more credentials need to be disclosed for both parties. HBTN speeds up subsequent negotiations between the entities that interact with each other frequently without impairing the privacy preservation.